2022
DOI: 10.1158/0008-5472.can-21-2187
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of RNA Helicases in DNA Damage Repair and Tumorigenesis Reveal Precision Therapeutic Strategies

Abstract: DEAD-box RNA helicases belong to a large group of RNA-processing factors and play vital roles unwinding RNA helices and in ribosomal RNA biogenesis. Emerging evidence indicates that RNA helicases are associated with genome stability, yet the mechanisms behind this association remain poorly understood. In this study, we performed a comprehensive analysis of RNA helicases using multiplatform proteogenomic databases. More than 50% (28/49) of detected RNA helicases were highly expressed in multiple tumor tissues, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…This was further validated in the drug sensitivity analysis, as demonstrated by the high percentage of negative correlation of RLBP expression with IC50 values of drugs involved in genome stability ( Figure 6 ). The concept is consistent with our previous findings showing that high expression of RNA helicases, DDX21, renders sensitivity for irinotecan, oxaliplatin, and etoposide [ 59 ]. Thus, overall high therapeutic sensitivity in patients would be expected along with better outcomes in CI.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This was further validated in the drug sensitivity analysis, as demonstrated by the high percentage of negative correlation of RLBP expression with IC50 values of drugs involved in genome stability ( Figure 6 ). The concept is consistent with our previous findings showing that high expression of RNA helicases, DDX21, renders sensitivity for irinotecan, oxaliplatin, and etoposide [ 59 ]. Thus, overall high therapeutic sensitivity in patients would be expected along with better outcomes in CI.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, DDX21, which is a significant RLBPs member, was revealed to engage in the HR pathway directly. The high expression of DDX21 leads to excessive sister chromatid exchanges [ 59 ]. PARP1 is required for chromosomal translocations; it displaces the Ku complex and initiates an alternative NHEJ pathway [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…DDX21 can effectively unwind R-loops (three-stranded coding RNA (lncRNA) HCP5 can limit the proliferation, migration, and invasion of gastric cancer cells by regulating the expression of DDX21 (40). Another study confirmed DDX21 as a prognostic marker for early colorectal cancer with microsatellite instability (41), which might be a new precision treatment strategy (42). Nevertheless, the role of DDX21 in different tumor types has not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…DDX21 acts as a sensor of nucleotide stress and contributes to melanoma development [ 31 ]. Furthermore, DDX21 plays its oncogenic role in colorectal cancer via inducing genome fragility, damaging double-strand repair and procrastinating HR repair [ 33 ]. In line with these findings, we also found that the high expression of DDX21 in gastric cancer leads to poor prognosis and disease progression of gastric cancer patients.…”
Section: Discussionmentioning
confidence: 99%